Dizionario Oxford study per studenti d'inglese - Ashby, Michael (Oxford University Press, 1998)
This bilingual dictionary is written specifically for Italian learners of English. Containing notes in Italian on vocabulary, grammar, and cultural differences, it guides the user through the traps faced by Italian students. This book is intended for italian learners of English